2009
DOI: 10.1128/iai.01390-08
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Pseudomonas aeruginosa Exotoxin A Is Dispensable for Cell Intoxication

Abstract: Exotoxin A is a major virulence factor of Pseudomonas aeruginosa. This toxin binds to a specific receptor on animal cells, allowing endocytosis of the toxin. Once in endosomes, the exotoxin can be processed by furin to generate a C-terminal toxin fragment that lacks the receptor binding domain and is retrogradely transported to the endoplasmic reticulum for retrotranslocation to the cytosol through the Sec61 channel. The toxin then blocks protein synthesis by ADP ribosylation of elongation factor 2, thereby tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 59 publications
4
23
0
1
Order By: Relevance
“…We detected only full-length toxins in the intoxicated cells and showed that the unnicked toxin (PE-furin) retains undiminished cytotoxicity. This indicates that furin cleavage is not critical for PE activity, at least in some cell types, which is consistent with several previous studies showing lack of correlation between proteolytic processing and PE toxicity [37,54]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We detected only full-length toxins in the intoxicated cells and showed that the unnicked toxin (PE-furin) retains undiminished cytotoxicity. This indicates that furin cleavage is not critical for PE activity, at least in some cell types, which is consistent with several previous studies showing lack of correlation between proteolytic processing and PE toxicity [37,54]. …”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, proteasome inhibition had slightly lower impact on A549 cells intoxicated with PE-NLS (37% decrease of viability), and there was only a very slight increase in vulnerability of lactacystin pre-treated HepG2 cells to PE-NLS intoxication, possibly due to strong accumulation of this mutein in the nucleus. Therefore, we conclude that proteasome degradation might play a role in both, stability of PE (as suggested previously [37]) and its cytotoxicity (similar to DT [38]).…”
Section: Resultssupporting
confidence: 83%
“…Low affinity for NAD ϩ in the full-length toxin is consistent with DT group toxins requiring activation by furin cleavage at an arginine-rich loop and/or reduction at disulfide bonds (46,47); however, it is clear both structurally and biochemically that full-length cholix is still capable of binding NAD ϩ , although relatively poorly. Interestingly, some recent studies claim that the toxicity of ExoA results from translocation of the full-length toxin directly across the endosome and into the cytoplasm (rather than via the retrograde pathway to the endoplasmic reticulum) and that the C-terminal fragment is unstable in the cytoplasm (48), casting some doubt on the conventional model. Notably, the K D1 for cholix c is in the same range as the…”
Section: Cholixmentioning
confidence: 99%
“…The exotoxin A produced by the bacterium Pseudomonas aeruginosa was also used. PE is formed by a single polypeptide of ϳ60 kDa containing three functional domains, an N-terminal domain containing regions able to bind cell surface structures, a C-terminal domain able to catalytically inactivate protein synthesis of the target cell, and a domain involved in transmembrane translocation (13). An intrachain disulfide bond is also present, whose reduction leads to the activation of the toxin inside the cell (possibly in the ER), and it has been reported that PDI (or members of the PDI family) could be involved in this process (14).…”
Section: Resultsmentioning
confidence: 99%